Compact self‐isolated MIMO antenna system based on quarter‐mode SIW cavity. Issue 10 (1st May 2019) - Niu, Bing‐Jian; Tan, Jie‐Hong
Abstract : A compact self‐isolated multiple‐input–multiple‐output (MIMO) antenna system is proposed. It is based on a quarter‐mode substrate integrated waveguide (SIW) cavity where two edges are shorted by metallic vias and the other edges are open. A narrow slot with a rotated angle of 45° is utilised to divide the single cavity into two equal eighth‐mode sub‐cavities. These sub‐cavities are fed by two coaxial ports to construct the proposed MIMO antenna system. A self‐isolated mechanism that cavity energy inputted by one port is radiated into free space rather than transmitted to the other port is first observed. High isolation between two antenna elements can be obtained without additional isolating or decoupling networks although they are contacted with each other. A fabricated prototype operating at 3.5 GHz achieves the measured port isolation of higher than 18.5 dB, envelope correlation coefficient (ECC) of less than 0.04, the peak gain of 4.6 dBi, and maximum efficiency of 79.2%. With advantages of compact size, high isolation, low ECC, and good radiation performance, the proposed self‐isolated MIMO antenna system is a good candidate for wireless communication.